When ways of life collide : multiculturalism and its discontents in the Netherlands - Sniderman, Paul M. (Princeton University Press, 2009)
In 2004, Dutch filmmaker Theo van Gogh was brutally murdered on a busy Amsterdam street. His killer was Mohammed Bouyeri, a twenty-six-year-old Dutch Moroccan offended by van Gogh's controversial film about Muslim suppression of women. The Dutch government had funded separate schools, housing projects, broadcast media, and community organizations for Muslim immigrants, all under the umbrella of multiculturalism. But the reality of terrorism and radicalization of Muslim immigrants has shattered that dream. In this arresting book, Paul Sniderman and Louk Hagendoorn demonstrate that there are deep conflicts of values in the Netherlands. In the eyes of the Dutch, for example, Muslims oppress women, treating them as inferior to men. In the eyes of Muslim immigrants, Western Europeans deny women the respect they deserve. Western Europe has become a cultural conflict zone. Two ways of life are colliding. Sniderman and Hagendoorn show how identity politics contributed to this crisis. The very policies meant to persuade majority and minority that they are part of the same society strengthened their view that they belong to different societies. At the deepest level, the authors' findings suggest, the issue that government and citizens need to be concerned about is not a conflict of values but a clash of fundamental loyalties.